2022
DOI: 10.1128/mbio.00918-22
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Species of Mycoplasma Endosymbionts Can Influence Trichomonas vaginalis Pathophysiology

Abstract: T. vaginalis and M. hominis form a unique case of endosymbiosis that modulates the parasite’s pathobiology. Recently, a new nonculturable mycoplasma species (“ Candidatus Mycoplasma girerdii”) has been described as closely associated with the protozoon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 100 publications
2
29
0
Order By: Relevance
“…A recent study reported that transcription of BspA-like proteins, surface proteins, and exosome proteins in T . vaginalis was modulated by Mycoplasma symbiosis [ 44 ], which implicates parasite pathogenicity. Therefore, we examined whether TH17 isolate contains Mycoplasma, showing that the Mycoplasma 16s rRNA gene was only amplified in the Mycoplasma-positive PM1 strain ( Fig 9A ) and Mycoplasma-like DNA puncta were only detected in the PM1 cytoplasm ( Fig 9B ), indicating that the TH17 isolate has no Mycoplasma symbiosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported that transcription of BspA-like proteins, surface proteins, and exosome proteins in T . vaginalis was modulated by Mycoplasma symbiosis [ 44 ], which implicates parasite pathogenicity. Therefore, we examined whether TH17 isolate contains Mycoplasma, showing that the Mycoplasma 16s rRNA gene was only amplified in the Mycoplasma-positive PM1 strain ( Fig 9A ) and Mycoplasma-like DNA puncta were only detected in the PM1 cytoplasm ( Fig 9B ), indicating that the TH17 isolate has no Mycoplasma symbiosis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Mycoplasma symbiosis was recently reported to correlate with the pathogenicity of T . vaginalis [ 44 ] and may increase parasite virulence. However, our results suggest that the symbiont is not the determinant conferring TH17 intrinsic cytoadherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that the microbial association with M. hominis, as well as with Ca. M. girerdii, could modulate the virulence of TV [ 53 ]. Our recent results did not confirm this; however, we did not clear the TVs from M. hominis to test the same isolate with and without symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…vaginalis was the only species in the reference data set representative of the Trichomonas genus, so it is possible that the particular species with increased gene expressed in macaques with ICD was not T. vaginalis'. Trichomonads do exhibit mucosal and host plasticity (Maritz et al, 2014). For example, T. vaginalis has been detected in the oral cavity (Costello et al, 2017) and respiratory tract (Duboucher et al, 2003).…”
Section: Introductionmentioning
confidence: 99%